THE POTENTIAL OF ARTIFICIAL INTELLIGENCE IN MANAGING INFORMATION NEEDS AND HARMFUL INFORMATION - Yunusova Minavvarhon Sabirovna (PT. Antis International Publisher, 2025)
Objective: This study investigates the strategic role of artificial intelligence (AI) in managing information needs and mitigating harmful information in the digital era, focusing on its implications for decision-making and societal well-being. Method: Using a qualitative approach, the research examines existing literature and case studies on AI applications in information management, with particular attention to its effectiveness in identifying, filtering, and countering harmful content, including cyberbullying and misinformation on social media. Results: The findings reveal that AI enhances information management by streamlining decision-making processes and safeguarding information security, especially for vulnerable groups such as children and adolescents. AI-driven systems demonstrate significant potential in detecting harmful information patterns, reducing the prevalence of digital violence, and promoting a healthier information ecosystem. Novelty: This study uniquely integrates the concepts of information needs and harmful information management through an AI-centric perspective, offering new insights into AI’s role in creating a secure and ethical digital environment.